2005
DOI: 10.1094/mpmi-18-0458
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Soybean Root Hairs After Infection by Bradyrhizobium japonicum

Abstract: Infection of soybean root hairs by Bradyrhizobium japonicum is the first of several complex events leading to nodulation. In the current proteomic study, soybean root hairs after inoculation with B. japonicum were separated from roots. Total proteins were analyzed by two-dimensional (2-D) polyacrylamide gel electrophoresis. In one experiment, 96 protein spots were analyzed by matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) to compare protein profiles between uninoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
124
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 69 publications
1
124
1
1
Order By: Relevance
“…For soybean, proteomic analyses to study nodulation have been applied to root hairs, 12,30) root hair-stripped roots, 12) nodule cytosol, 20) nodule mitochondria, 19) the peribacteroid membrane, 17) xylem sap, 21) and apoplast. 21) Although there were many differences in the sampling and harvesting time points for the studies, our proteome images proved to be similar to those of root hairs, root hair-stripped roots, and nodule cytosol and mitochondria, and the lists of proteins identified also partly overlapped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For soybean, proteomic analyses to study nodulation have been applied to root hairs, 12,30) root hair-stripped roots, 12) nodule cytosol, 20) nodule mitochondria, 19) the peribacteroid membrane, 17) xylem sap, 21) and apoplast. 21) Although there were many differences in the sampling and harvesting time points for the studies, our proteome images proved to be similar to those of root hairs, root hair-stripped roots, and nodule cytosol and mitochondria, and the lists of proteins identified also partly overlapped.…”
Section: Discussionmentioning
confidence: 99%
“…Through proteomic analysis, several studies have reported identification of symbiosis-related proteins in various plant materials: root and root hairs, [11][12][13][14] nodules, [14][15][16] the peribacteroid membrane, 17,18) nodule mitochondria, 19) the nodule cytosol, 20) xylem, 21) and apoplast. 21) However, most of these studies focused on the protein profile of the specific organelle or tissue at a defined time point, especially at the early stage of nodulation, and development of indeterminate nodules.…”
mentioning
confidence: 99%
“…Eighty-three percent of the proteins identified were obtained through comparisons with clustered M. truncatula EST sequences. Since the root hair is the site of initial rhizobial infection, Wan et al [61] developed a method to isolate soybean root hairs in sufficient quantity for proteomic analysis. Their data identified 16 root hair proteins whose abundance increased within 12 h of inoculation by Bradyrhizobium japonicum.…”
Section: Database (Url)mentioning
confidence: 99%
“…Proteomic investigations into nodule biology complement parallel transcription-profiling studies by revealing subtleties that might reflect differential levels of gene regulation. Soybean, Lotus and Medicago have been the subject of numerous proteomic studies [61][62][63]64 ]. These studies were targeted to various tissues during development or under biotic and abiotic elicitation.…”
mentioning
confidence: 99%
“…We also used 40 proteins (600 mg) extracted from soybean (cv Williams 82) and root hair, which were separated by 2-DE (24 cm IPG strip, linear pH 4-7), according to the method Trypsin (trypsinogen) Bovine P00760 described in ref. [14]. Four replicates were performed and gel pictures were analyzed using Phoretix (nonlinear dynamics, v2005).…”
Section: Samplesmentioning
confidence: 99%